Adaptive Management in International Development - Knowledge Base - Prieto Martin, Pedro (2025)
A curated collection of resources on Adaptive Management and MEL in International Development

Working between systems and complexity - a practitioners guide - Allen, Will (learningforsustainability.net, 2025)
How practitioners navigate between systems and complexity thinking. Exploring structure and emergence in real-world collaboration and adaptive work.

Monitoring, Evaluation and Learning for Systems Change - McDonald, Lizzy; Simpson, Kate; Schramm, Carolin (Wasafiri, 2025)
Today’s critical challenges are complex and require system level change. Issues like ending poverty, reversing biodiversity collapse, creating more equitable and sustainable food systems, or ending health inequalities, will not respond to neat siloed technical interventions. These are not problems we can tackle head on. Rather, we need to change the conditions (systems) that create these problems. Consequently, many of the most ambitious philanthropic foundations are adopting ‘systems change’ approaches to their work. There is a critical need to better understand the impact of systems change interventions. This is for two reasons: 1) without being able to understand our impact we can’t learn about the efficacy of efforts and focus on doing more helpful action and less unhelpful action, and 2) without effective monitoring and evaluation it is hard to galvanise resources, whether as money, time, or enthusiasm. Traditional monitoring, evaluation and learning (MEL) approaches and practices struggle to respond to complexity. Many of today’s MEL approaches have been developed to serve funders keen to ‘prove’ the efficacy of their work and hold grantees accountable. This paradigm has produced approaches like ‘logical frameworks’ that seek to create a linear logic between intervention, outputs, outcomes and impact. Such approaches often pay scant regard to the activity (intentional or otherwise) of other actors in any system, and don’t adapt well to the characteristics of complex problems such as emergence, uncertainty, and interdependency. There is a fast-developing body of practice on MEL for systems change. A growing number of practitioners are experimenting with complexity informed approaches to MEL, and UNDP is pioneering an open-source set of tools and ideas.ii Wasafiri is contributing to this innovation by developing a MEL approach that builds on our (open access) Systemcraft Framework. iii Emerging approaches for systems change MEL are underpinned by some key principles. There is growing consensus on the need to be pragmatic and flexible, not just because it is a new field for many that requires a degree of mindset and behaviour change and different ways of working. MEL approaches for system change primarily focus on improving and learning and on identifying ways to adapt and pivot. This contrasts with linear approaches to implementation and measurement. Learning questions guide and co-exist alongside indicators to support continual learning and adaptation. These shifts will require a shift in relationships between funders and implementers from measuring and accountability to greater flexibility and patience, close engagement and learning together. There is pressure to show impact in less time. Reduced time horizons, increasing impatience and integration of new sets of agendas in development programming present challenges in the context of systems change. In an increasingly resource constrained context and amid growing global uncertainty (e.g. current global politics, emergencies like COVID, economic instability, rapid technological advancement), it is unclear which direction donors will take, i.e. an even greater focus on value for money and impact, and/or willingness to explore innovative approaches and learning in uncertain territory. Wasafiri’s approach for systems MEL builds on Systemcraft. This is a diagnostic and design tool for systems change, that has been used globally across a broad range of systems and interventions. This paper summarises our approach to MEL for systems change. It aims to provide a short introductory overview and form a ‘conversation starter’ to initiate a practical dialogue on current practices, experiences, and learnings with MEL for systems change. It introduces some concepts and appropriate tools for measuring systems change and poses some key questions for further discussion. We aim to engage with funders and practitioners working on complex problems who are in the process of or planning to develop their approach to and practices for MEL, who are interested to learn, share and explore. We welcome your inputs, either in response to this document, via a call, or during online webinars that we will convene in 2025.

Fast Isn’t the Same as Forward - Brink (Brink's Cognitive Download, 2025)
What it takes to create smart velocity

Evaluative Inquiry for Systemic Change: A Guide to Shift Beyond Fixes to Lasting Value - Gates, Emily F.; Vidueira, Pablo (SAGE Publications, Inc, 2025)
In a world where social, ecological, health, and other problems are influenced by multiple, intersecting systems, why do most interventions target single-factor solutions? Why does so much evaluation settle for incremental change, and how could it contribute instead to deeper, lasting, transformative change? Authors Emily F. Gates and Pablo Vidueira make two interconnected arguments in this book: they critique the "fixed" approach of traditional program evaluation and policy analysis, and they advance an alternative approach centered on changing systems and developing the value of efforts toward change. They demonstrate that systemic change that embeds evaluative inquiry is a theoretically supported, practical way to work toward fundamental social change with lasting impact.

Track to Change | Home - Clear Horizon (Clear Horizon, 2025)
Track to Change homepage

Evaluation handbook: 2025 edition - Directorate-General for International Partnerships (European Commission); Hassnain, Hur; McHugh, Karen; Lorenzoni, Marco; Alvarez, Valentin; Augustyn, Anna Maria; Davies, Rick; Rogers, Patricia; Buchanan-Smith, Margie (Publications Office of the European Union, 2025)
The Evaluation Handbook – 2025 Edition reflects the European Commission’s steadfast commitment to promoting a culture of results, accountability, and learning across the EU’s external action. As one of the world’s leading development and international cooperation actors, the European Commission bears a particular responsibility to ensure that its interventions are informed by robust evidence, deliver tangible results, and represent the highest standards of transparency and effectiveness in the use of public funds. Building on the foundations laid by the 2024 edition— which itself constituted a major revision of the 2006 Methodology Guidance—the 2025 edition reflects the continuous evolution of the European Commission’s evaluation practice over the past two decades. It draws on international best practices, incorporates state-of-the-art methodological advances, and acknowledges the increasingly multifaceted nature of development cooperation. This Handbook is attuned to the dynamic policy, institutional, and geopolitical environment in which EU external action operates, offering an adaptive and forward-looking framework to support high-quality evaluations that are both credible and consequential. This Handbook reaffirms evaluation as an indispensable pillar of the EU’s commitment to better regulation, performance-based management, and evidence-informed decision-making. It provides practical and strategic guidance to support evaluation managers, partners, and stakeholders in navigating the full evaluation cycle—from design and implementation to dissemination and uptake of findings.
Keywords: EU action; International policy; aid evaluation; cooperation policy; coordination of aid; development aid; food security; report; the EU's international role; user guide